Decision-making in additive manufacturing supply chains: a systematic literature review - Abu-Abdoun, Dana I.; Ekren, Banu Y.; Matopoulos, Aristides (Elsevier, 2025)
Additive Manufacturing (AM) is reshaping supply chain (SC) structures by enabling decentralised production, digital inventories, and on-demand manufacturing. These transformations demand new decision-making approaches to manage disruptions in SC configuration, inventory management, supplier selection, and manufacturing design. This study systematically reviews 27 peer-reviewed studies to assess decision-support tools—such as optimisation models, simulation techniques, and multi-criteria decision-making (MCDM) frameworks—used to facilitate AM integration. A structured mapping is proposed to map AM-induced SC changes to appropriate decision tools. The findings provide structured insights to enhance SC performance, adaptability, and resilience in AM-enabled environments.
11th IFAC Conference on Manufacturing Modelling, Management and Control MIM 2025: 30 June – 3 July 2025, Trondheim, Norway
Keywords: 4014 Manufacturing Engineering; 40 Engineering; Generic health relevance; 9 Industry, Innovation and Infrastructure; 4007 Control engineering, mechatronics and robotics; 4008 Electrical engineering; Additive Manufacturing; Supply Chain Management; Decision-Making; Multi-Criteria Decision Making; Decision Support Systems